Effect of lower extremity amputation on cardiovascular hemodynamic environment: An in vitro study. (December 2022) - Li, Xiao; Li, Zhongyou; Jiang, Wentao; Wei, Junru; Xu, Kairen; Bai, Taoping
Abstract: Lower extremity amputation (LEA) was associated with a greater risk of cardiovascular disease, but its hemodynamic mechanisms have not been fully studied. Therefore, to clarify the interrelationship between them, and figure out the potential pathogenesis, the exploration of the hemodynamic environment change of patients after LEA was premeditatedly executed. A near-physiological mock circulatory system (MCS) was employed in the present work to replicate the cardiovascular circulation after LEA in a short time and the unsteady-state numerical simulation was utilized as an auxiliary method to observe the changes of the hemodynamic environment inside the blood vessel. Higher severity of LEA leads to higher peripheral vascular impedance, higher blood pressure, and more obvious redistribution of blood perfusion volume. In addition, higher severity of LEA leads to lower wall shear stress (WSS), higher oscillatory shear index (OSI), and higher relative residence time (RRT) appeared in the infrarenal abdominal aorta and the iliac artery, while these changes are closely related to the higher probability of cardiovascular diseases. Results showed that different degrees of LEA (varying heights, unilateral/bilateral) have diverse effects on the patient's hemodynamic environment. This study explained the potential pathogenesis of cardiovascular diseases after LEA from a hemodynamic perspective and provided a certain reference value for the improvement of the cardiovascular hemodynamic environment and the prevention of cardiovascular diseases in lower extremity amputees.